Nonlinear differential equation and analytic function spaces. Issue 1 (2nd January 2018) - Li, Hao; Li, Songxiao
Abstract : In this paper we consider the nonlinear complex differential equation where, , are analytic in the unit disk, for all . We investigate this nonlinear differential equation from two aspects. On the one hand, we provide some sufficient conditions on coefficients such that the analytic solutions of this equation belong to the space. On the other hand, we find growth estimates for the analytic solutions of this equation if the coefficients satisfy some conditions.